First Record of Eurythenes Obesus (Chevreux, 1905) (Amphipoda, Lysianassoidea, Eurytheneidae) in Brazilian Waters - Senna, André R. (Arquivos do Museu Nacional, 2021)
Currently, 14 lysianassoid species are known from the Brazilian waters. Material collected from the Campos Basin, off Rio de Janeiro State, Brazil, during the “Campos Basin Deep-Sea Environmental Project” coordinated by CENPES/PETROBRAS were analyzed. The samples were collected using a semi- balloon door trawl at 1300 and 1608 m depth, aboard of the N/R Astro Garoupa. Eurythenes obesus (Amphipoda: Lysianassoidea: Eurytheneidae) was found in these samples and is herein redescribed. The species is widely distributed around the world, but there are no previous records of this species from Brazilian waters.